2016
DOI: 10.1080/17415349.2016.1245119
|View full text |Cite
|
Sign up to set email alerts
|

Heatstroke – providing evidence-based advice to dog owners

Abstract: With increasing summer temperatures and milder winters, the risk of heatstroke in dogs is growing. Veterinary nurses have a vital role in identifying high risk patients and advising owners of the risks of heatstroke. Nurses are able to recommend preventative measures and first aid necessary to minimise the risk of heatstroke; in addition to increasing the chances of survival where heatstroke does occur. This article will provide an overview of the evidence that can be presented to owners during nursing consult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Reports from Israel suggest exertional HRI may be the more common cause of heatstroke in dogs in that country [ 24 , 25 , 26 ]. Although there is some evidence that exertion is also the main trigger of HRI in UK dogs [ 27 ], current efforts to educate UK dog owners about heatstroke prevention focus almost exclusively on environmental heatstroke, specifically the message that ‘dogs die in hot cars’ [ 28 ]. Generation of a solid evidence base on the predominant trigger of canine HRI, canine risk factors for different HRI types and the seasonality of different HRI types in the UK could support optimized and targeted educational campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…Reports from Israel suggest exertional HRI may be the more common cause of heatstroke in dogs in that country [ 24 , 25 , 26 ]. Although there is some evidence that exertion is also the main trigger of HRI in UK dogs [ 27 ], current efforts to educate UK dog owners about heatstroke prevention focus almost exclusively on environmental heatstroke, specifically the message that ‘dogs die in hot cars’ [ 28 ]. Generation of a solid evidence base on the predominant trigger of canine HRI, canine risk factors for different HRI types and the seasonality of different HRI types in the UK could support optimized and targeted educational campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…One veterinary hospital has reported an increase in the number of dogs presenting with exertional heatstroke (caused by exercise) compared to environmental heatstroke (typically following vehicle confinement), with 73% of recent cases being categorised as exertional heatstroke (Bruchim et al, 2017), compared to 58% of cases previously reported (Aroch et al, 2009). The increase in popularity of amateur canine sports participation in the UK, combined with increasing episodes of warm weather during traditionally colder months in autumn and early spring (WMO, 2017), could potentially increase the risk of canine exertional heatstroke occurring (Hall and Carter, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As the popularity of canine sports continues to increase (The Kennel Club, 2016) there is an increased risk of exertional heat stroke occurring (Hall and Carter, 2016). The ability to measure canine athlete temperatures during training and racing events is essential for identifying those at risk of heat injury, as rapid treatment has been shown to reduce mortality (Bruchim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%